2019
DOI: 10.1186/s13014-019-1337-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metastases within the hypothalamic-pituitary area in patients with brain metastases

Abstract: Aim To quantify the prevalence of brain metastases involving the hypothalamic-pituitary (HT-P) area. Introduction Cognitive impairment and fatigue are common side effects of whole brain irradiation (WBI) comprising the quality of life (QoL) for survivors. While the former is related to radiation-induced hippocampal injury, the latter could be secondary to hormonal disbalance as a consequence of radiation of the HT-P area. Thus, sparing both regions from higher irradiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
(54 reference statements)
2
8
0
Order By: Relevance
“…Gondi et al deemed hippocampus sparing WBRT safe with an estimated risk of peri-hippocampal metastases of 8.6% [36]. Our group has recently analyzed 865 patients with 4280 metastases and showed an incidence of involvement of the HT-P area of approximately 4% [37]. Against that background, an approach of sparing the HT-P area in addition to the hippocampus during WBRT appears reasonable.…”
Section: Discussionmentioning
confidence: 71%
“…Gondi et al deemed hippocampus sparing WBRT safe with an estimated risk of peri-hippocampal metastases of 8.6% [36]. Our group has recently analyzed 865 patients with 4280 metastases and showed an incidence of involvement of the HT-P area of approximately 4% [37]. Against that background, an approach of sparing the HT-P area in addition to the hippocampus during WBRT appears reasonable.…”
Section: Discussionmentioning
confidence: 71%
“…Regarding HPA involvement, there are limited data in brain-metastases literature. Janssen et al [ 32 ] analyzed an extensive series of 4280 metastases from 865 patients and found the rate of hypothalamic and pituitary metastases to be 0.6% and 0.2%, respectively. Because the available data are so limited, there is still much uncertainty regarding recurrence risks and the risk-to-benefit ratio.…”
Section: Discussionmentioning
confidence: 99%
“…These studies should aim to: (i) evaluate in greater detail the cognitive effects and, more generally, the quality of life impairment during and immediately after WBRT; (ii) study the mechanisms producing these “early” effects; (iii) test in “clinical studies” advanced RT techniques based on both hippocampal-sparing and hypothalamic-pituitary-sparing, currently evaluated only in “planning studies” [ 196 , 199 , 200 , 201 ]; (iv) test new timings of antiglutamatergic drugs administration (e.g., start memantine a few weeks before WBRT), aimed at preventing not only late toxicity but also the acute effects; (v) compare stereotactic RT versus HA-WRT plus memantine based on data showing a reduced risk of CD in patients with 4–15 BMs treated with stereotactic RT compared to standard WBRT +/− memantine [ 202 ].…”
Section: Discussionmentioning
confidence: 99%